The practice of Canaanite cult : the Middle and Late Bronze Ages - Susnow, Matthew. (Münster)
374 sayfa
Keywords: “This richly illustrated book explores Canaanite religion and ritual from an archaeological perspective. It sheds new light on the use of space within southern Levantine temples as well as the religious ideologies motivating the behavioral patterns identified in those cultic contexts. Religion and ritual are both universalistic and particularistic. The aim of this study is to arrive at a more holistic understanding of MB and LB religion in the southern Levant. To achieve this goal, this book is organized into three main parts: (1) where Canaanite cultic activities were conducted; (2) what activities and rituals were performed within Canaanite cultic spaces; and (3) why and how those activities were conducted in those spaces. The central thesis of this book is that Canaanite religion was remarkably responsive and adaptive and was reflective of the diversity of the various micro-regions in the southern Levant. This study has arrived at five new observations regarding Canaanite cult as practiced in Canaanite temples. First, temple architecture and the activities conducted within temples were neither static temporally nor interregionally. Cultic spaces in the southern Levant were responses to different particular circumstances and situations. The settings, locations and the construction types of temples related to, affected, and were affected by the rituals and activities that were conducted in those spaces. A second insight in this study is that ritual in the southern Levant was highly responsive and adaptive. The diachronic changes noted throughout the MB and LB in temple architecture, temple locations, ritual activities as well as in iconography and material culture unquestionably reflect changing cultural, geopolitical and socioeconomic phenomena. A third insight is that in contrast to Mesopotamian, Hittite and Egyptian temples, temples in the southern Levant remarkably do not reflect the concept of the house of the god. Neither the layout of Canaanite temples nor the activities performed within the temples reflect the layouts or activities of southern Levantine domestic spaces. A fourth insight: Rather than perceiving Canaanite cultic spaces as the houses and residences of deities, it seems these spaces functioned as venues for hosting feasts and commensal meals based around sacrifice and other ritual activities. These were therefore spaces within which social cohesion and group unity were forged. Depending on who controlled the temples, these spaces could also function as tools for creating and maintaining social and ritual hierarchy and inequality. A fifth observation relates what Canaanites did to why. Social behaviors and organization were controlled and maintained through ritual, feasting, commensality, the competitive and public presentation of offerings, and through the use of iconography. However, these actions were also informed by Canaanite religious ideology. Temples in the southern Levant functioned as conduits for initiating contact with the divine. Rather than the divine presence of deities being contained within temples, there was an effort to entice the deities out of temples in order to transform the entire landscape into a religious and sacred landscape“ --